2017
DOI: 10.1097/cin.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Relationships Between Health-Related Problems and Online Health Information Seeking

Abstract: Online health information seeking (OHIS) functions as a coping strategy to relieve health-related stress and problems. When people rate their health as poor or felt concern about their health, they frequently visit the Internet to seek health-related information in order to understand their symptoms and treatments. Regarding this role of OHIS, it is important to understand the relationships between health-related problems and OHIS. This study applies the Common-Sense Model as a theoretical lens to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
(34 reference statements)
2
21
0
Order By: Relevance
“…Nevertheless, the accuracy of keyword or search term identification depends on information-seeking behavior which are influenced by media trends, outbreak news briefs, disease occurrence, and Internet penetration [8,9,10,11,13,15,16,23]. Information-seeking behavior also is influenced by individual variables such as age, sex, level of education, cultural aspect, language, social class, marital status, level of healthcare utilization, and level of stress [23,25,26,27]. An additional factor that drives the information-seeking behavior is keyword suggestion in Google.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the accuracy of keyword or search term identification depends on information-seeking behavior which are influenced by media trends, outbreak news briefs, disease occurrence, and Internet penetration [8,9,10,11,13,15,16,23]. Information-seeking behavior also is influenced by individual variables such as age, sex, level of education, cultural aspect, language, social class, marital status, level of healthcare utilization, and level of stress [23,25,26,27]. An additional factor that drives the information-seeking behavior is keyword suggestion in Google.…”
Section: Discussionmentioning
confidence: 99%
“…[121337] In addition, individuals with high levels of health anxiety are exposed to disturbing and confusing information; hence, they use a variety of health information sources to find a sense of tranquility and confidence. [20] Moreover, it can be claimed that in order to better understand their health; interact with the doctor; learn more about diseases, treatments, and medications prescribed; and decide on referral to a doctor,[12] people with high health anxiety perform seeking more purposefully and seek for health information such as symptoms associated with illnesses, different treatment strategies, drug prescription, and awareness of nutrition-related issues.…”
Section: Discussionmentioning
confidence: 99%
“…[1618] It can also be said that when people are exposed to stresses and concerns about their health status, and their minds are engaged with illness-related concerns, in order to track their health status and eliminate these concerns, they seek health information through various sources of information such as newspapers, TVs, the Internet, radios, and health-care professionals. [37]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internet is often used by those experiencing health-related stress and problems and to seek health-related information in order to understand their symptoms and treatments [15]. Facebook is often used for seeking social support and research has shown that if the support was perceived in adolescents, this decreased their depressed moods, however, if not perceived, this had adverse effects and increased their depressed moods [1].…”
Section: Introductionmentioning
confidence: 99%